MARKETING COMMUNICATION STRATEGY FOR FLICKA BAGS PRODUCTS VIA INSTAGRAM SOCIAL MEDIA - DAUD, ROSY FEBRIANI (Universitas Sang Bumi Ruwa Jurai, 2024)
Technological developments make it easy to get information in internet access supported by the existence of several social media chat applications that have changed the pattern of selling goods by entrepreneurs. Online product marketing communication strategies through Instagram accounts are the focus of research in writing this journal. The @flickabags account uses Instagram as an online marketing communication medium in carrying out its business promotion. This research is to find out the marketing communication strategy for Flicka Bags products through Instagram social media. The method used in this research is descriptive qualitative method. While the theory used is marketing communication theory. In conclusion, the marketing communication strategy for Flicka Bags products through Instagram social media Flicka Bags utilizes Instagram in carrying out an online marketing communication strategy by utilizing the features available on Instagram.